2000
DOI: 10.1021/jm9911478
|View full text |Cite
|
Sign up to set email alerts
|

7-Methyl-6,7,8,9,14,15-hexahydro-5H-benz[d]indolo[2,3-g]azecine:  A New Heterocyclic System and a New Lead Compound for Dopamine Receptor Antagonists

Abstract: Partially hydrogenated derivatives of the new heterocyclic ring systems benz[d]indolo[2,3-g]azecine and bisindolo[3,2-d][2, 3-g]azecine were synthesized starting from lactones and amines via the described synthetic methods. In binding assays with rat striatal receptors, 7-methyl-6,7,8,9,14,15-hexahydro-5H-benz[d]indolo[2, 3-g]azecine (LE 300) proved to be of high affinity for the D(1) binding site (K(i) = 0.08 nmol for displacement of [(3)H]SCH23390), being superior in this assay to standards such as butaclamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 6 publications
1
45
0
Order By: Relevance
“…Compound LE300 was synthesized in the group of Dr Jochen Lehmann (Bonn, Germany), according to Witt et al 14 All other compounds and reagents were obtained at Sigma Chemical unless otherwise stated.…”
Section: Methodsmentioning
confidence: 99%
“…Compound LE300 was synthesized in the group of Dr Jochen Lehmann (Bonn, Germany), according to Witt et al 14 All other compounds and reagents were obtained at Sigma Chemical unless otherwise stated.…”
Section: Methodsmentioning
confidence: 99%
“…Previous radioligand binding experiments have shown that LE 300 (pK i = 7.79 [5] ) is about 6-up to 51-fold less potent than the reference 5-HT 2A -receptor antagonist ketanserin (pK i = 9.41 [17] , 8.46 [18] , 8.93 [19] , 8.80 [20] ). The antagonist potency ratio of 1:17 determined in our functional rat tail artery assay perfectly matches with this range although the absolute affinity tends to be moderately higher (pA 2 = 8.32 versus 9.55, see Table 1).…”
Section: In Vitro Pharmacologymentioning
confidence: 99%
“…These compounds represent hybrid molecules of tryptamine and phenethylamine, linked through the moderately rigid azecine ring system [5] . In radioligand binding studies the most prominent member of this series, compound LE 300 (Chart 1) displays subnanomolar affinity for the rat striatal D 1 receptor and a well-balanced binding profile at D 2 and 5-HT 2A receptors, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…1) introduced by Lehmann et al [15], revealed a subnanomolar affinity towards the rat striatal D 1 receptor and high functional activity at the 5-HT 2A receptor [15 -17]. The idea behind the synthesis of such a heterocyclic system was to incorporate the substructures of tryptamine and bphenylethylamine moieties into a moderately constrained ten-membered semi-rigid azecine ring [15].…”
Section: Introductionmentioning
confidence: 99%
“…1) introduced by Lehmann et al [15], revealed a subnanomolar affinity towards the rat striatal D 1 receptor and high functional activity at the 5-HT 2A receptor [15 -17]. The idea behind the synthesis of such a heterocyclic system was to incorporate the substructures of tryptamine and bphenylethylamine moieties into a moderately constrained ten-membered semi-rigid azecine ring [15]. Intensive SAR studies were performed within this novel class of dopamine receptor ligands, including variations in ring size [18], de-indolization of the structure [19], the insertion of an additional oxygen atom into the alicyclus [20,21] and changing one of the aromatic moieties (indole replaced by benzene, thiophene, and 1-methyl-1H-pyrrole, respectively) and its location with respect to each other at the central alicyclic ring [22].…”
Section: Introductionmentioning
confidence: 99%